2015
DOI: 10.3947/ic.2015.47.4.225
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Evaluation of Group A Streptococcus Isolated from Children with Pharyngitis: A Study from Iran

Abstract: BackgroundThe aim of this study was to evaluate the antibiotic susceptibility of Group A streptococcus (GAS) to antibiotics usually used in Iran for treatment of GAS pharyngitis in children.Materials and MethodsFrom 2011 to 2013, children 3-15 years of age with acute tonsillopharyngitis who attended Mofid Children's Hospital clinics and emergency ward and did not meet the exclusion criteria were enrolled in a prospective study in a sequential manner. The isolates strains from throat culture were identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
2
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 18 publications
5
17
2
4
Order By: Relevance
“…The national AMR surveillance center reported lower levels (7.2%) of erythromycin resistance in isolates from 85 hospitals across Thailand in 2018. 36 The resistance levels in our study are lower than those reported from India (46%), 37 Iran (33.9%), 33 and South Korea (25.7%), 38 similar to those from Greece (18.8%) 12 but higher than those from the United States (6.8%). 13 Reports of macrolide resistance are causing concern and limiting their use as empirical treatment for sore throats.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…The national AMR surveillance center reported lower levels (7.2%) of erythromycin resistance in isolates from 85 hospitals across Thailand in 2018. 36 The resistance levels in our study are lower than those reported from India (46%), 37 Iran (33.9%), 33 and South Korea (25.7%), 38 similar to those from Greece (18.8%) 12 but higher than those from the United States (6.8%). 13 Reports of macrolide resistance are causing concern and limiting their use as empirical treatment for sore throats.…”
Section: Discussionmentioning
confidence: 42%
“…In our study, we found that all of our isolates were sensitive to penicillin and ceftriaxone, despite reports of ceftriaxone resistance emerging from Iran, which needs further exploration and confirmation, as historically GAS has been fully susceptible to penicillins and cephalosporins. [33][34][35] Erythromycin resistance was found in 2/11 (18.2%) GAS isolates, an important antibiotic for the treatment of pharyngitis in those with penicillin allergies. The national AMR surveillance center reported lower levels (7.2%) of erythromycin resistance in isolates from 85 hospitals across Thailand in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Лечение такого тон-зиллита подразумевает симптоматические средства -купирование болевого синдрома при его наличии, мест-нодействующие антисептики, а также снижение высокой температуры, если она есть [2]. [17][18][19]. Данное состояние также уместно назвать острым тонзиллитом, однако лечение в такой ситуации отличает-ся принципиально и последствия несвоевременного, неверного лечения достаточно серьезны.…”
Section: в чем проблема?unclassified
“…15-30% детей и около 5-15% взрослых [17], необходимо постоянное обучение врачей, своевре-менное ознакомление их с изменениями чувствительно-сти флоры к антибиотикам и регулярный мониторинг результатов их работы [12,15,19].…”
Section: большинство специалистов и медицинских сообществ занимающихunclassified
See 1 more Smart Citation